Exome analysis and functional classification of identified variants in racing Quarter Horses - Curi, R. A. [UNESP]; Pereira, G. L. [UNESP]; Alvarez, M. V. N. [UNESP]; Baldassini, W. A. [UNESP]; Machado Neto, O. R. [UNESP]; Chardulo, L. A. L. [UNESP] (Wiley-Blackwell, 2020)
The main objectives of this study were to identify and functionally classify SNPs and indels by exome sequencing of animals of the racing line of Quarter Horses. Based on the individual genomic estimated breeding values (GEBVs) for maximum speed index (SImax) obtained for 349 animals, two groups of 20 extreme animals were formed. Of these individuals, 20 animals with high GEBVs for SImax and 19 with low GEBVs for SImax had their exons and 5 ' and 3 ' UTRs sequenced. Considering SNPs and indels, 105 182 variants were identified in the expressed regions of the Quarter Horse genome. Of these, 72 166 variants were already known and 33 016 are new variants and were deposited in a database. The analysis of the set of gene variants significantly related (P-adjusted < 0.05) to extreme animals in conjunction with the predicted impact of the changes and the physiological role of protein product pointed to two candidate genes potentially related to racing performance:SLC3A1on ECA15 andCCN6on ECA10.
Keywords: equine; indel; molecular marker; SNP; speed index